Dynamics of Food Self-Sufficiency and Stunting: Evidence Jember Regency Indonesia - Woro Astuti, Sri Juni; Pranata Putra, Allen (Iapa Proceedings Conference, 2024)
The urgency of this research lies in the need for a deeper understanding of the factors that cause high stunting in areas that are nominally successful in food self-sufficiency. This study also seeks to fill the literature gap by directly linking food self-sufficiency policies and children's health conditions, especially in the context of stunting. Furthermore, this study reviews two main problem formulations, namely: 1) What are the dynamics of food self-sufficiency and stunting rates in Jember Regency? 2) How to optimize the stunting reduction policy strategy in Jember Regency? This research method uses qualitative with in-depth interview data collection techniques, this research analysis technique uses data triangulation. The implications of these findings emphasize the importance of adopting a more holistic and cross-sectoral policy approach. Efforts to reduce stunting in Jember must be integrated with food security policies that pay attention to nutritional quality, as well as effective health and education programs. Local governments need to strengthen coordination between sectors and involve communities in policy implementation to ensure that the benefits of food self-sufficiency can be felt by all levels of society, especially the most vulnerable.